Myrcia (Myrtaceae) in the Vale Natural Reserve, Linhares, Espírito Santo, Brazil - Scaravelli,Fernanda Savioli (2022)
Abstract Myrcia (Myrteae, Myrtaceae) is represented by 101 species in the Brazilian state of Espírito Santo, but local floristic surveys on this genus still lack in this centre of diversity and endemism. In this context, a taxonomic account of Myrcia in the Vale Natural Reserve (VNR), Linhares, Espírito Santo, is presented. Forty-six species were registered in this study, representing 46% of the richness of the genus in Espírito Santo. Twenty-five species (54%) are endemic to the Atlantic domain and seven are endemic to Espírito Santo. Myrcia scytophylla is reported in the Atlantic forest for the first time and M. cymatophylla, M. congestiflora, and M. ferruginosa are new occurrences in the state. Species composition revealed by this study considerably differs from that of a previous checklist. Representatives of Myrcia can be found in all main vegetation types of the VNR and the anthropic areas. The study site must be considered prioritary for conservation of Myrcia due to the presence of a rich assemblage, which also includes restrict and threatened species.